2016
DOI: 10.1097/md.0000000000004669
|View full text |Cite
|
Sign up to set email alerts
|

Gout increases risk of fracture

Abstract: There is still debate on whether high uric acid increases bone mineral density (BMD) against osteoporotic fracture or bone resorption caused by gout inflammation. This study aimed to evaluate whether gout offers a protective effect on bone health or not. We conducted a nationwide population-based retrospective cohort study to evaluate the association between gout history and risk factors of fracture.A retrospective cohort study was designed using the claim data from Longitudinal Health Insurance Database (LHID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Numerous quantitatively based studies debating the association between gout and the risk of fractures remain inconclusive. Tzeng et al [23] reported that gout history increased the fracture risk, which was consistent with the results of a Chinese adult-based research conducted by Wang et al [24]. However, the relationship became variable when focus on different fracture sites in the study performed by Paik et al [17], in which the risk of fractures raised in the hip but not in the wrist.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Numerous quantitatively based studies debating the association between gout and the risk of fractures remain inconclusive. Tzeng et al [23] reported that gout history increased the fracture risk, which was consistent with the results of a Chinese adult-based research conducted by Wang et al [24]. However, the relationship became variable when focus on different fracture sites in the study performed by Paik et al [17], in which the risk of fractures raised in the hip but not in the wrist.…”
Section: Introductionsupporting
confidence: 72%
“…After 326 studies excluded by duplicates, 2291 excluded by reading titles and abstracts, and 32 studies were downloaded and carefully checked by reading full texts. After careful reading, five articles [1, 17, 2325] involving eight datasets were considered to be qualified for the quantitative analysis of the association of gout with the risk of fractures, and four articles [1, 23, 26, 28] were considered to be qualified for the quantitative analysis of the association of urate-lowering with the risk of fractures. The inclusion processes and reasons for exclusion were depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This large observational study with long follow-up used data from a nationally representative cohort, and therefore, the findings are likely to be generalisable to a broader population. The finding that there is no link between gout and risk of fragility conflicts with an earlier Taiwanese study that reported a 17% higher risk of fracture in people with gout compared with controls 2. However, the Taiwanese study included all fracture sites (including ankle and foot) rather than only fragility fractures.…”
Section: Contextmentioning
confidence: 85%